Identification of Circular RNAs and Their Targets in Leaves of Triticum aestivum L. under Dehydration Stress - Wang, Yuexia; Yang, Ming; Wei, Shimei; Qin, Fujun; Zhao, Huijie; Suo, Biao (Frontiers in Plant Science, 2017)
Circular RNAs (circRNAs) are a type of newly identified non-coding RNAs through high-throughput deep sequencing, which play important roles in miRNA function and transcriptional controlling in human, animals and plants. To date, there is no report in wheat seedlings regarding the circRNAs identification and roles in the dehydration stress response. In present study, the total RNA was extracted from leaves of wheat seedlings under dehydration-stressed and well-watered conditions, respectively. Then, the circRNAs enriched library based deep sequencing was performed and the circRNAs were identified using bioinformatics tools. Around 88 circRNAs candidates were isolated in wheat seedlings leaves while 62 were differentially expressed in dehydration-stressed seedlings compared to well-watered control. Among the dehydration responsive circRNAs, six were found to act as 26 corresponding miRNAs sponges in wheat. Sixteen circRNAs including the 6 miRNAs sponges and other 10 randomly selected ones were further validated to be circular by real-time PCR assay, and 14 displayed consistent regulation patterns with the transcriptome sequencing results. After Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway analysis of the targeted mRNAs functions, the circRNAs were predicted to be involved in dehydration responsive process, such as photosynthesis, porphyrin and chlorophyll metabolism, oxidative phosphorylation, amino acid biosynthesis and metabolism, as well as plant hormone signal transduction, involving auxin, brassinosteroid, and salicylic acid. Herein, we revealed a possible connection between the regulations of circRNAs with the expressions of functional genes in wheat leaves associated with dehydration resistance.